Logging contractors' growth in the southern cone: an analysis of contractor business strategies, innovation, and mechanization - Mac Donagh, Patricio Miguel (2019)
Forest plantations have increased in South America for several decades. Harvesting is performed mainly through contractor companies. Our hypothesis is that logging contractors that innovate, grow more than others. We analyzed logging contractors through production and innovation, working in Argentina (22), Brazil (35) and Uruguay (10), through surveys between 2008 and 2012. Factors that affected firm growth were analyzed with linear mixed effect models. In all three countries there was a preponderance of logging contractors with cellulose companies. Our results show that logging firms that had mutualistic supply chain relations with the contracting organizations had better production indicators and lower cost per ton than other independent harvesting contractors. In the last 10 years, mechanization increased significantly, reducing the number of employees. Innovation was the most significant variable in enhanced logging production. For the period from 10 to 5 years before the survey period, the number of employees and type of contracting company were most significant on loggers' growth. During the last 5-year period before the survey period, the number of employees and innovation were significant. Thus, during the last 10 years, logging companies shifted from growth based on type of the firm to the amount of innovation by firms, and contracting companies.